Healthy Living for Elders: Are You at Risk for Drug Interactions? - Jennifer Hillan (EDIS)
Drugs (prescription medications, over-the-counter products, vitamins, minerals, and herbals) may interact with each other or the food you eat and cause harmful reactions. To see if you are at risk for drug interactions, circle Yes or No for the questions provided in this document. This is document FCS 8621-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.